A model of emulsion plugging ability in sandpacks: Yield pressure drop and consistency parameter. (16th January 2020) - Ding, Boxin; Dong, Mingzhe; Yu, Long
Abstract: In this study, a total of 20 sandpack flood tests, each with 11 different flow rates, were conducted to evaluate oil-in-water (O/W) emulsion plugging ability in sandpacks. Four conditions of emulsion flow in porous media were observed, identified, and discussed, in terms of the capillary number. A general model for the pressure drop versus flow rate based on the bi-viscosity model was developed from a comprehensive analysis of the experimental data. This model expresses that the flow of emulsion in porous media has two distinct mobility in porous media demarcated by a critical pressure drop. The inverse of the mobility is determined as consistency parameter and the critical pressure drop as the yield pressure drop. Effects of interfacial tension (IFT), emulsion quality, droplet size, emulsion slug size, and sandpack permeability on the yield pressure drop and consistency parameter were experimentally and numerically investigated. The newly proposed model has a good agreement between the predicted and experimental plugging pressure drop of emulsion. Besides giving guides on preparation of O/W emulsions and injection strategies in a specific oil reservoir, use of the proposed model can also help model reservoir scale O/W emulsion flow to reduce or shut-in the mobility in thief zones.